1992
DOI: 10.1002/ijc.2910510508
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gallbladder cancer: A polish case‐control study

Abstract: A population-based case-control study of gallbladder cancer was conducted in the south-west of Poland, within the frame-work of the SEARCH Programme of the International Agency for Research on Cancer. A total of 73 cases and 186 controls were interviewed using a questionnaire including demographic and socio-economic factors, education, smoking, alcohol, tea and coffee consumption, and past medical history. A validated diet history was used to estimate the daily intake of calories, fats, carbohydrates, proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
87
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 21 publications
5
87
3
Order By: Relevance
“…Our study, based on 157 cases, found no strong evidence for an association between green-yellow vegetables or fruit intake. This is consistent with a previous cohort mortality study conducted in Japan (Hirayama, 1981), although case -control studies have reported significant protective effects for fruit and vegetables (Kato et al, 1989) and intakes of vitamins C and E (Zatonski et al, 1992). Our study also found no evidence for a strong association between fruit and vegetables consumption and pancreas cancer mortality, which is consistent with other cohort studies (Hirayama, 1981;Zheng et al, 1993;Shibata et al, 1994;Ziegler et al, 1996;Stolzenberg-Solomon et al, 2002), although the numbers of cases in all of these studies, including ours, may be too small to detect a moderate association.…”
Section: Discussionsupporting
confidence: 92%
“…Our study, based on 157 cases, found no strong evidence for an association between green-yellow vegetables or fruit intake. This is consistent with a previous cohort mortality study conducted in Japan (Hirayama, 1981), although case -control studies have reported significant protective effects for fruit and vegetables (Kato et al, 1989) and intakes of vitamins C and E (Zatonski et al, 1992). Our study also found no evidence for a strong association between fruit and vegetables consumption and pancreas cancer mortality, which is consistent with other cohort studies (Hirayama, 1981;Zheng et al, 1993;Shibata et al, 1994;Ziegler et al, 1996;Stolzenberg-Solomon et al, 2002), although the numbers of cases in all of these studies, including ours, may be too small to detect a moderate association.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to gallstones, the risk factors for gallbladder cancer, such as obesity, insulin resistance, high-fat or high-caloric diet and altered lipid metabolism tend to run in families 8,9,12,32 (Hsing AW, Rashid A, Sakoda L, Deng J, Han T, Wang BS, Shen MC, Fraumeni JF Jr., Gao YT. Gallstones and the risk of biliary tract cancer: a population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic and familial predisposition suggests the role of genetic predisposition or shared metabolic and lifestyle factors, including obesity, insulin resistance, or high-fat, high-caloric diet. 1,[6][7][8] Familial aggregation of gallstones has been reported in several studies, [9][10][11] but only one assessed the role of family history of gallstones in biliary tract cancer etiology. A case-control study of gallbladder cancer in Bolivia and Mexico reported that a family history of gallstones was associated with a 3.6-fold risk of gallbladder cancer.…”
mentioning
confidence: 99%
“…We identified eight cohort studies Wolk et al, 2001;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Engeland et al, 2005;Kuriyama et al, 2005;Oh et al, 2005) and four case -control studies (Zatonski et al, 1992(Zatonski et al, , 1997Strom et al, 1995;Serra et al, 2002) that reported results on overweight/obesity and risk of gallbladder cancer. One case -control study (Zatonski et al, 1992) was excluded because this study was included in a multicentre case -control study (Zatonski et al, 1997); the multicentre casecontrol study was included in this meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…One case -control study (Zatonski et al, 1992) was excluded because this study was included in a multicentre case -control study (Zatonski et al, 1997); the multicentre casecontrol study was included in this meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%